Fiscal Decentralization, Commitment and Regional Inequality: Evidence from State-level Cross-sectional Data for the United States - Akai, Nobuo; Hosio, Masayo (Journal of Income Distribution®, 2009)
Conventional approaches to fiscal decentralization suggest that decentralizationlowers the power of redistribution, but recent theoriesargue that fiscal decentralization can work as a commitment device.The former effect is argued to cause an increase in inter-county inequality,while the latter suggests a decrease.This article first clarifies the relationship between fiscal decentralizationand inter-county inequality by using cross-sectional data for theUnited States. Our result indicates that the achievement of autonomyby fiscal decentralization in poor (low-income) counties contributes todecreased inter-county inequality, but that this effect is not as large asthe dominating adverse effect fiscal decentralization has on rich (highincome)counties.